Determined the Concentration Elements to Human Nail Using X- Ray Fluorescence Technique - Al-saedi, Jamal K.; Hasan, Nada M.; AbdAlhasan, Ali A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
Cancer constitutes a serious disease and a major health problem in worldwide, a lot of people were infected with this dangerous disease, Therefore, there must be attention to this disease through diagnosis and prevention there. In this study, we determined the relationship between the Cancer and the concentration of trace elements by comparing the concentration trace elements for infected and non-infected people. The trace elements concentrations to nails are one of the diagnostic criteria that easily to detect and dated this disease without any harm to the patient. Eight nails samples were collected from cancer-infected and eight samples from non-infected of the relatives of first-degree. All samples were measured by the concentrations elements using X-ray fluorescence. The accuracy and precision were verified using standard samples. The results showed that the average concentrations of elements (Magnesium, silicon, potassium, calcium, ironand selenium,) were lower for cancer patients than their non-infected relatives and the trace elements (zinc, copper, cadmium, lead, chromium, manganese) were higher for cancer patients than their non-infected relatives. In conclusion, we need further studies to confirm the relationship between trace elements and cancer disease and attention the effect of diet and environmental risk of cancer.